THE ROLE OF ART AS A TOOL FOR EMPOWERMENT OF GYPSY WOMEN (Tabanque. Revista Pedagógica, 2018)
The socio-educational intervention allows for locating, knowing and acting on the different human contexts, in order to favor the inclusion of the groups that define society. Based on this idea, the following are the bases of a study accomplished during the 2016-2017 academic year, in collaboration with the Department of Art History of the University of Valladolid, on the role of art as a tool for empowerment of gypsy women, carried out through a theoretical phase and the staging of a practical phase with a group of gypsy women from Palencia. This project raises, in short, the need to use art as a tool of liberation in the face of the social pressure to which women are still subjected today, as well as a means of recognition, acceptance and empowerment in the eyes of society, in such a way that each woman has the possibility of recognizing the female genealogy within the scope of her culture and creation, as well as of expressing her desires, thoughts and ideas towards a path that leads them into full social equality.
Keywords: Art; empowement; gypsy ethnic group; women; socio-educational intervention